The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5194/wes-2019-31
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of tip spacing, thrust coefficient and turbine spacing inmulti-rotor wind turbines and farms

Abstract: Large eddy simulations (LES) are performed to study the wakes of a multi-rotor wind turbine configuration comprising of four identical rotors mounted on a single tower. The multi-rotor turbine wakes are compared to the wake of a conventional turbine comprising of a single rotor per tower with the same frontal area, hub height and thrust coefficient. The multi-rotor turbine wakes are found to recover faster, while the turbulence intensity in the wake is smaller, compared to the wake of the conventional turbine.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it is observed that closely spacing the rotors on a multi‐rotor wind turbine increases the loading on the blades which requires a further examination by means of aeroelastic simulation of a multi‐rotor wind turbine 7 . An aerodynamic analysis of a multi‐rotor wind turbine comprised of four rotors indicate faster wake recovery as well as reduced turbulence kinetic energy (TKE) compared to a single‐rotor wind turbine with equal swept area 10–13 . The reduction of TKE in multi‐rotor wind turbine wake has the potential of reduced fatigue loads on the downstream wind turbines in a wind farm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is observed that closely spacing the rotors on a multi‐rotor wind turbine increases the loading on the blades which requires a further examination by means of aeroelastic simulation of a multi‐rotor wind turbine 7 . An aerodynamic analysis of a multi‐rotor wind turbine comprised of four rotors indicate faster wake recovery as well as reduced turbulence kinetic energy (TKE) compared to a single‐rotor wind turbine with equal swept area 10–13 . The reduction of TKE in multi‐rotor wind turbine wake has the potential of reduced fatigue loads on the downstream wind turbines in a wind farm.…”
Section: Introductionmentioning
confidence: 99%
“…7 An aerodynamic analysis of a multi-rotor wind turbine comprised of four rotors indicate faster wake recovery as well as reduced turbulence kinetic energy (TKE) compared to a single-rotor wind turbine with equal swept area. [10][11][12][13] The reduction of TKE in multi-rotor wind turbine wake has the potential of reduced fatigue loads on the downstream wind turbines in a wind farm.…”
mentioning
confidence: 99%